Studies on length-weight relationship of hill stream fish, Pseudecheneis sulcata (Mccelland, 1842) from the snow-fed Tamor river in Eastern Nepal (Our Nature, 2025)
The present paper aims to describe the length-weight (LW) relationship of the hill stream fish Pseudecheneis sulcata. Fish of various lengths and weights were collected from the Tamor River in Eastern Nepal from December 1 to 15, 2024. A total of 42 fish specimens were stored in a freezer and then transported to the Ichthyological Laboratory at the Department of Zoology, Degree Campus, Biratnagar. The measurements of the fish samples were conducted with maximum accuracy. The data obtained from the measurements were analyzed using the formula. The estimated slope value (b) for the total length and weight in the length-weight relationship is 3.410, indicating positive allometric growth. This suggests that under optimal conditions for growth, as the length increases, there is a proportionately greater increase in weight.